Tandem solar cell

JP7606599B2Active Publication Date: 2024-12-25LONGI GREEN ENERGY TECH CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2023512693
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-20
Filing Date
2021-08-19
Publication Date
2024-12-25
Estimated Expiration
2041-08-19

AI Technical Summary

Benefits of technology

【0024】 本開示が解決しようとする技術的課題、技術的解決手段及び有益な効果をより明確にするために、以下、図面及び実施例を参照して、本開示をさらに詳細に説明する。なお、ここで説明する特定実施例は本開示を解釈するためのものに過ぎず、本開示を限定するものではない。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007606599000003
    Figure 0007606599000003
  • Figure 0007606599000004
    Figure 0007606599000004
  • Figure 0007606599000005
    Figure 0007606599000005
Patent Text Reader

Abstract

A tandem solar cell is provided that improves the photoelectric conversion efficiency of the tandem solar cell by forming a functional layer with a high degree of film order on the bottom cell. [Solution] The tandem solar cell of the present invention includes a bottom cell having a textured surface, a hole transport layer formed on the textured surface of the bottom cell, a second ordering-inducing layer and a perovskite absorber layer formed on the hole transport layer, the second ordering-inducing layer being located between the hole transport layer and the perovskite absorber layer, and a transparent conductive layer formed on the perovskite absorber layer. The inducing material contained in the second ordering-inducing layer is an organic ammonium salt or an inorganic lead compound. The tandem solar cell of the present invention is a tandem solar cell with a perovskite solar cell as the top cell.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] <CROSS REFERENCE TO RELATED APPLICATIONS> This disclosure claims priority to a Chinese patent application entitled "Tandem Solar Cell," application number 202010855550.7, filed with the China Patent Office on August 20, 2020, the entire contents of which are incorporated herein by reference.

[0002] TECHNICAL FIELD This disclosure relates to the field of photovoltaics, and more particularly to tandem solar cells. [Background technology]

[0003] Single-junction solar cells can often only absorb sunlight of a certain wavelength. In order to improve the utilization rate of sunlight, multiple solar cells with different bandgaps can be connected in series through a composite layer to absorb sunlight of different wavelengths. Perovskite cells have a wide bandgap, and the bandgap of the absorption spectrum of the perovskite cell can be adjusted by adjusting the compounding ratio of the components. Thus, perovskite cells are suitable as the top cell of a tandem solar cell.

[0004] When combining a perovskite cell with a bottom cell having a textured structure, how to form a highly ordered functional layer of film on the bottom cell is a challenge in improving the photoelectric conversion efficiency of the tandem solar cell. Summary of the Invention [Problem to be solved by the invention]

[0005] An object of the present disclosure is to provide a tandem solar cell that improves the photoelectric conversion efficiency of the tandem solar cell by forming a functional layer having a high degree of order of film on a bottom cell. [Means for solving the problem]

[0006] In order to achieve the above object, the present disclosure provides a tandem solar cell, which includes a bottom cell having a textured surface, a hole transport layer formed on the textured surface of the bottom cell, a second ordering inducer layer and a perovskite absorber layer formed on the hole transport layer, the second ordering inducer layer being located between the hole transport layer and the perovskite absorber layer, and a transparent conductive layer formed on the perovskite absorber layer. The inducer material contained in the second ordering inducer layer is an organic ammonium salt or an inorganic lead compound.

[0007] By adopting the above technical solution, the perovskite absorption layer is grown on the second ordering induction layer, and the buffering effect of the second ordering induction layer can prevent the perovskite absorption layer from being adversely affected by the molecular disorder on the surface of the hole transport layer. In addition, the perovskite absorption layer can be grown in an ordered manner due to the induction effect of the second ordering induction layer, and has high crystallinity and large crystal grain size. In this case, the perovskite absorption layer has few defects and high photoelectric conversion efficiency. In addition, the second ordering induction layer, as an intermediate layer between the hole transport layer and the perovskite absorption layer, can reduce the energy level difference between the films, achieve an energy level matching favorable to hole transport, and improve the hole transport performance of the tandem solar cell.

[0008] When the inducing material of the second ordering-inducing layer is an organic ammonium salt or an inorganic lead compound, the organic ammonium salt and the inorganic lead compound have a good match with the crystal structure of the perovskite material of the perovskite absorption layer and are similar in properties, so that the growth of a highly ordered perovskite absorption layer can be easily induced.

[0009] In some possible embodiments, the inorganic lead compound is one or more of lead oxide, lead bromide, lead iodide, lead chloride, lead acetate, lead thiocyanate and lead sulfide. These inorganic lead compounds are metal oxides and have good compatibility with the metal oxide hole transport layer, so that good interface contact can be achieved between the second ordering-inducing layer and the hole transport layer. In addition, the inorganic lead compounds and the perovskite material of the perovskite absorber layer are both lead compounds, so that they have good compatibility, so that the second ordering-inducing layer can easily induce the growth of the perovskite absorber layer.

[0010] In some possible embodiments, the second ordering-inducing layer has a thickness of 1 nm to 20 nm.

[0011] In some possible embodiments, the tandem solar cell further comprises a first ordering-inducing layer, the first ordering-inducing layer being located between the bottom cell and the hole transport layer.

[0012] Similar to the mechanism of action of the second ordering-inducing layer, the interface buffering and inducing action of the first ordering-inducing layer allows the hole transport layer to grow in an orderly manner with higher crystallinity and larger grain size, thereby reducing the crystal grain size and defects of the hole transport layer and improving the hole transport performance of the hole transport layer. In addition, the first ordering-inducing layer, as an intermediate layer between the hole transport layer and the bottom cell, can reduce the energy level difference between the films and achieve an energy level matching favorable for hole transport between the hole transport layer and the bottom cell, thereby improving the hole transport performance of the tandem solar cell.

[0013] When the inducing material of the first ordering-inducing layer is a rod-shaped molecular material, the rod-shaped molecular material is easily stacked closely to stand upright on the lower film, forming a highly ordered geometric channel. This highly ordered geometric channel can induce the upper organic film to grow along the geometric channel through strong interaction. At this time, the first ordering-inducing layer containing the rod-shaped molecular material exerts a good ordered growth induction effect on the upper film. Furthermore, since the rod-shaped molecular material has properties similar to liquid crystal in a thin film, and the temperature of its liquid crystal phase is low, a large-area highly ordered first ordering-inducing layer can be easily formed at a low temperature by utilizing the mobility of the liquid crystal.

[0014] In some possible embodiments, the inductive material contained in the first ordering-inducing layer is a metal oxide, and the material of the hole transport layer is an inorganic hole transport material.

[0015] By adopting the above technical solution, since the metal oxide is an inorganic material and has similar material properties to the inorganic hole transport layer made of inorganic materials, a good interface contact can be formed between the first ordering-inducing layer and the hole transport layer, the compatibility is good, and the ordered growth of the hole transport layer is more easily induced.

[0016] In some possible embodiments, the thickness of the first ordering-inducing layer is 1 nm to 20 nm. In the first ordering-inducing layer with this thickness, the rod-like molecular material or the like is likely to have properties similar to liquid crystal, and thus an ordered large-area film is likely to be formed.

[0017] In some possible embodiments, the rod-shaped molecular material is BPTT and the metal oxide is zinc oxide.

[0018] In some possible embodiments, the material of the hole transport layer includes one or more of PTAA, Cz2T, Spiro-OMeTAD, Spiro-TTB, copper phthalocyanine, and nickel oxide.

[0019] In some possible embodiments, the hole transport layer has a thickness of 5 nm to 100 nm.

[0020] In some possible embodiments, the process for forming the first ordering-inducing layer, the second ordering-inducing layer and the hole transport layer is one or more of a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process or a hydrothermal nanoparticle synthesis process.

[0021] In some possible embodiments, the method of forming a perovskite absorber layer described above comprises: forming lead iodide and cesium bromide on the second ordering-inducing layer by a co-evaporation deposition method; Spraying a mixed solution of formamidine iodide and formamidine hydrobromide on the lead iodide and cesium bromide to form a perovskite material film; and annealing the perovskite material film to form a perovskite absorber layer.

[0022] The above description is merely an outline of the technical solutions of the present disclosure. In order to more clearly grasp the technical solutions of the present disclosure, the technical solutions of the present disclosure can be implemented based on the contents of the specification. In order to make the above and other objectives, features and advantages of the present disclosure more easily comprehensible, the following provides specific embodiments of the present disclosure. [Brief description of the drawings]

[0023] The drawings described herein are provided for a further understanding of the present disclosure, constitute a part of the present disclosure, and illustrative embodiments of the present disclosure and the description thereof are used to interpret the present disclosure and do not constitute undue limitations on the present disclosure. [Figure 1] FIG. 1 is a structural schematic diagram of a tandem solar cell according to an embodiment of the present disclosure. [Diagram 2]1 is a schematic diagram of the molecular structures of BPTT and Cz2T according to an embodiment of the present disclosure, where a is a schematic diagram of the structure of BPTT and b is a schematic diagram of the structure of Cz2T. [Diagram 3] FIG. 1 is a structural schematic diagram of a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 4] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Diagram 5] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 6] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 7] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 8] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 9] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 10] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 11] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 12] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 13] 1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. [Figure 14]1A to 1C are schematic diagrams illustrating the states at each stage of a method for manufacturing a p-type crystalline silicon-perovskite tandem solar cell according to an embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In order to clarify the technical problems, technical solutions and advantageous effects of the present disclosure, the present disclosure will be described in more detail below with reference to the drawings and examples. Note that the specific examples described herein are merely for the purpose of interpreting the present disclosure and are not intended to limit the present disclosure.

[0025] It should be noted that when an element is described as being "fixed" or "disposed" on another element, the element may be directly located on the other element or indirectly located on the other element. When an element is described as being "connected" to another element, the element may be directly connected to the other element or indirectly connected to the other element.

[0026] Furthermore, terms such as "first", "second", etc. are used for descriptive purposes only and do not indicate or imply the relative importance or number of such technical features. Thus, a feature qualified by "first" or "second" explicitly or implicitly includes one or more of such features. In the description of this disclosure, "plurality" means two or more, unless otherwise specifically limited. "several" means one or more, unless otherwise specifically limited.

[0027] In describing the present disclosure, the orientations or positional relationships indicated by terms such as "upper," "lower," "front," "rear," "left," and "right" are based on the orientations or positional relationships shown in the drawings, and are merely for the purpose of conveniently or simply describing the present disclosure. They do not indicate or imply that such devices or elements are necessarily in a particular orientation or are configured or operated in a particular orientation, and should not be understood as limiting the present disclosure.

[0028] In the description of the present disclosure, unless otherwise clearly specified or limited, the terms "attach", "connect to each other", "connection" and the like should be understood broadly, for example, fixed connection, detachable connection, or integral connection. Mechanical connection or electrical connection is also possible, and direct connection or indirect connection via an intermediate medium may be possible, and may be internal communication between two elements or an interaction relationship between two elements. Those skilled in the art can understand the specific meaning of the above terms in the present disclosure according to the specific situation.

[0029] At present, crystalline silicon cells, as the mainstream product in the photovoltaic power generation field, belong to the technology of high-efficiency crystalline silicon solar cells, and their cell efficiency (26.7%) is close to their theoretical limit efficiency (29.4%). With the further development of photovoltaic power generation technology, it has been confirmed that tandem solar cell technology is an effective means to exceed the efficiency of conventional crystalline silicon solar cells.

[0030] Organic-inorganic hybrid perovskite solar cells have attracted widespread attention worldwide as a new type of high-efficiency, low-cost solar cell. In just a few years, the photoelectric conversion efficiency of perovskite solar cells has rapidly increased from 3.8% in 2009 to more than 25%, approaching the efficiency of commercially available silicon-based solar cells. In perovskite cells, the band gap of the absorption spectrum of the perovskite cell can be adjusted within the range of 1.5 eV to 1.8 eV by adjusting the composition of the components, making the perovskite cell a suitable tandem top cell. It is expected that a crystalline silicon-perovskite tandem solar cell, which combines a perovskite cell with a crystalline silicon cell, can achieve a photoelectric conversion efficiency of more than 30%. Currently, there are documents that confirm that the conversion efficiency of a crystalline silicon-perovskite tandem solar cell can reach more than 25%.

[0031] A crystalline silicon-perovskite tandem solar cell uses a crystalline silicon cell as the bottom cell to absorb the energy of sunlight with a wavelength of 800nm ​​to 1200nm, and a perovskite cell as the top cell to absorb the energy of sunlight with a wavelength of 300nm to 800nm. A two-end series battery is formed by connecting the bottom cell and the top cell through a composite layer, and the open circuit voltage of the entire tandem solar cell is the sum of the voltages of the top cell and the bottom cell, and the current of the tandem solar cell is the minimum current of the top cell and the bottom cell, at which time good current matching is required between the top cell and the bottom cell.

[0032] In the prior art, in perovskite cells, each functional layer of the device is manufactured by a solution spin-coating method. High-efficiency crystalline silicon bottom cells generally use a light-confining structure of a double pyramidal textured surface to improve the absorption and utilization rate of solar light, and improve the cell conversion efficiency. When manufacturing a perovskite top cell on a crystalline silicon bottom cell with a textured surface structure, the light-confining structure of the micron-scale pyramidal textured surface of the crystalline silicon bottom cell is a challenge for manufacturing the perovskite top cell by a solution method. The problem is that the thickness of each functional layer of a perovskite battery is generally several hundred nanometers, so that the material of each functional layer in the solution state is easily accumulated at the bottom of the pyramidal textured surface, and therefore each functional layer is difficult to deposit uniformly on the micron-scale pyramidal textured surface by a solution spin-coating method. Currently, a solution is generally adopted in which the crystalline silicon bottom cell is polished to reduce the roughness of the textured surface in contact with the perovskite top cell, thereby enabling the perovskite top cell to be manufactured by a solution method. Although this method can fabricate a perovskite top cell by solution spin-coating on a crystalline silicon bottom cell, it sacrifices the gain in cell efficiency due to the textured surface structure and its light trapping effect, and the polishing process significantly increases the overall cell manufacturing cost.

[0033] Whether each functional layer (hole transport layer, perovskite absorption layer, electron transport layer, hole blocking layer, electrode buffer layer, electrode, etc.) of the perovskite top cell is uniformly deposited on the textured surface of the crystalline silicon bottom cell is an important parameter when fabricating the perovskite top cell on the textured surface of the crystalline silicon bottom cell. Compared with the solution processing method, the vacuum deposition process can deposit various vapor-depositable functional materials on various substrates, so the vacuum deposition process is suitable for fabricating the perovskite top cell on the textured surface of the crystalline silicon bottom cell.

[0034] In the conventional manufacturing process of crystalline silicon-perovskite tandem solar cells, the hole transport layer is directly grown on the tunnel composite layer. The tunnel composite layer is usually made of inorganic materials such as highly doped microcrystalline silicon. The materials of the hole transport layer can be divided into two types: organic semiconductors such as 2,2',7,7'-tetrakis(di-p-tolylamino)-9,9'-spirobisfluorene (spiro-TTB) and inorganic semiconductors such as nickel oxide. When various types of hole transport materials are directly grown on the inorganic tunnel composite layer, due to the high degree of molecular disorder on the surface of the tunnel composite layer made of inorganic materials and the difference in material properties existing in the organic materials, there are many nucleation sites for the material molecules of the hole transport layer on the surface of the tunnel composite layer, and it is easy to form small island-like growth structures. In this case, the manufactured hole transport layer has problems such as low lattice matching, large grain boundary defects, poor interface contact performance, and poor film order, and as a result, the hole transport performance of the hole transport layer is poor. These problems mainly lead to the abrupt growth of the film due to the poor compatibility of the hole transport layer and the tunnel composite layer and the high degree of disorder of the tunnel composite layer. Similarly, the perovskite absorber layer is often deposited directly on the hole transport layer. When the hole transport layer is made of an inorganic semiconductor material, the perovskite material of the perovskite absorber layer, as an organic-inorganic hybrid material, has compatibility problems with nickel oxide. If the perovskite material is deposited directly on the inorganic material, the disorder of the inorganic material increases the number of crystal nucleation sites of the perovskite material, causing the growth of small crystal grains and deteriorating the controllability of the film growth. From the above, whether it is a hole transport layer or a perovskite absorber layer, there are problems such as poor interface compatibility, small crystal grain size, and low degree of order of the film. These defects have a negative effect on the performance of each functional layer and tend to reduce the photoelectric conversion efficiency of the tandem solar cell.

[0035] As can be seen from the above, the key to improving the photoelectric conversion efficiency of a tandem solar cell is how to form each functional layer with a high degree of order in the film on the bottom cell.

[0036] To solve the above problems, an embodiment of the present disclosure provides a tandem solar cell, which may be, but is not limited to, a tandem solar cell with a perovskite cell as a top cell and any one of a crystalline silicon cell, a polysilicon cell, a single crystal silicon ingot cell, a CIGS cell, a perovskite cell, a gallium arsenide cell, and an organic solar cell as a bottom cell.

[0037] As shown in FIG. 1, a tandem solar cell according to an embodiment of the present disclosure includes a bottom cell 10, a first ordering-inducing layer 31, a hole transport layer 32, a second ordering-inducing layer 33, a perovskite absorption layer 34 and a transparent conductive layer 36, which are stacked in sequence.

[0038] As shown in FIG. 1, the bottom cell 10 may be any one of the bottom cells described above that may be used in a tandem solar cell. The bottom cell 10 may be an n-type solar cell or a p-type solar cell. Regardless of the structure or type, the bottom cell 10 may have a textured surface. The textured surface may be formed on the front or back surface of the bottom cell 10 by a texturing process. Specifically, the textured surface structure may be a pyramidal textured surface, an inverted pyramidal textured surface, etc.

[0039] Taking a crystalline silicon battery as an example, the structure of the bottom cell may include a p-type crystalline silicon wafer or an n-type crystalline silicon wafer with a pn junction formed thereon. The p-type crystalline silicon wafer or the n-type crystalline silicon wafer with a pn junction is the light absorbing layer of the bottom cell, which absorbs sunlight and converts photons into photogenerated carriers. The front and back surfaces of the p-type crystalline silicon wafer or the n-type crystalline silicon wafer with a pn junction may be formed with a textured surface structure by a texturing process.

[0040] As shown in Figure 1, the tandem solar cell may further include a tunnel composite layer 20 located on the bottom cell 10 to enable tunnel composite collection of photogenerated carriers of the bottom cell 10 and the perovskite top cell. The tunnel composite layer 20 may be a tunnel composite layer 20 made of transparent metal oxides such as tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), tungsten-doped indium oxide (IWO), titanium-doped indium oxide (ITIO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), etc.

[0041] The tunnel composite layer 20 may be a tunnel composite layer 20 made of highly doped microcrystalline silicon opposite the pn junction of the bottom cell 10. For example, the tunnel composite layer 20 may be made of an n-type doped microcrystalline silicon layer and a p-type doped microcrystalline silicon layer, where the p-type doped microcrystalline silicon layer is in direct contact with the hole transport layer 32, and the n-type doped microcrystalline silicon layer is in direct contact with the bottom cell 10. Specifically, the n-type doped microcrystalline silicon layer may be a phosphorus doped microcrystalline silicon layer, and the p-type doped microcrystalline silicon layer may be a boron doped microcrystalline silicon layer.

[0042] 1, in practical application, the tunnel composite layer 20 can be manufactured by one of the following processes: plasma enhanced chemical vapor deposition (PECVD), magnetron sputtering, hot filament chemical vapor deposition, and catalytic chemical vapor deposition. Since the bottom cell 10 has a textured surface, the tunnel composite layer 20 grown on the bottom cell 10 will also have a textured surface structure.

[0043] As shown in Fig. 1, the above-mentioned first ordering-inducing layer 31 is formed on the tunnel composite layer 20. It should be noted that in practical applications, the first ordering-inducing layer 31 may also be omitted. The process for forming the first ordering-inducing layer 31 may be one or more of magnetron sputtering process, laser pulse deposition process, thermal evaporation deposition process, chemical vapor deposition process, solution deposition process, gel-sol deposition process, or hydrothermal nanoparticle synthesis process.

[0044] As shown in Fig. 1, in order to improve the degree of order of the first ordering-inducing layer 31, the parameters such as the thickness of the first ordering-inducing layer 31 are adjusted so that the inducing material used to manufacture the first ordering-inducing layer 31 has properties similar to liquid crystal, so that a large-area ordered film can be formed, which is favorable for improving the degree of order of the first ordering-inducing layer 31. When the first ordering-inducing layer 31 has a high degree of order, it is favorable for the ordered growth of the hole transport layer 32 thereover, which can reduce the defects of the hole transport layer 32 and improve the hole transport performance.

[0045] For example, when the thickness of the first ordering-inducing layer 31 is 1 nm to 20 nm, the first ordering-inducing layer 31 is an extremely thin film, and the inducing material of the first ordering-inducing layer 31 is likely to exhibit properties similar to those of liquid crystal in the extremely thin film, which makes it easy to form a large-area ordered film by utilizing the fluidity of liquid crystal, which is advantageous for improving the degree of order of the first ordering-inducing layer 31. The thickness of the first ordering-inducing layer 31 may be 1 nm, 5 nm, 8 nm, 10 nm, 12 nm, 18 nm, 20 nm, etc.

[0046] As shown in FIG. 1, the hole transport layer 32 is formed on the first ordering-inducing layer 31. The process for forming the hole transport layer 32 may be one or more of a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process, or a nanoparticle synthesis process by a hydrothermal method. The thickness of the hole transport layer 32 may be 5 nm to 100 nm. For example, the thickness of the hole transport layer 32 may be 5 nm, 10 nm, 30 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, etc.

[0047] As shown in FIG. 1, the hole transport layer 32 is induced by the van der Waals effect of the first ordering-inducing layer 31 to form on the first ordering-inducing layer 31 and has a specific orientation, phase state and ordered aggregate state structure.

[0048] As shown in FIG. 1, since the above-mentioned first ordering-inducing layer 31 has weak epitaxial ability, a lattice matching relationship can be formed between the first ordering-inducing layer 31 and the hole transport layer 32 through weak epitaxial interaction (van der Waals effect), thereby inducing ordered growth of the hole transport layer 32, and thereby realizing control of the microstructure of the hole transport layer 32.

[0049] As shown in FIG. 1, in practical applications, in order to form a highly ordered first ordering-inducing layer 31 and to give the first ordering-inducing layer 31 a good ordering-inducing effect, a rod-shaped molecular material may be used as the inducing material of the first ordering-inducing layer 31 to induce a hole transport layer 32 made of an organic hole transport material. The rod-shaped molecular material is easily upright in the lower film (tunnel composite layer 20) by densely stacking, and a highly ordered geometric channel is formed. Moreover, the rod-shaped molecular material has properties similar to liquid crystal in a thin film, and the temperature of its liquid crystal phase is low, so that it is easy to form a highly ordered large-area film at a relatively low temperature by utilizing the fluidity of the liquid crystal. From the above, the rod-shaped molecular material is easy to form a highly ordered first ordering-inducing layer 31 due to its molecular characteristics and liquid crystal characteristics, and therefore has an excellent ordering growth-inducing effect. Specifically, the rod-shaped molecular material can be selected as biphenylthiophene (BPTT). BPTT can form structurally stable geometric channels that can induce the growth of highly ordered and stable films.

[0050] In practical application, the metal oxide may be used as the inducing material of the first ordering-inducing layer 31 to induce the hole transport layer 32 made of an inorganic hole transport material. In this case, the metal oxide is an inorganic material and has similar material properties to the inorganic hole transport layer 32 made of an inorganic material, so that a good interface contact can be achieved between the first ordering-inducing layer 31 and the hole transport layer 32, the compatibility is good, and it is easier to induce the ordered growth of the hole transport layer 32. Specifically, the metal oxide may be zinc oxide.

[0051] The material of the hole transport layer 32 may include, but is not limited to, one or more of PTAA, Cz2T, Spiro-OMeTAD, Spiro-TTB, copper phthalocyanine, and nickel oxide.

[0052] As an example, when the inducing material molecules of the first ordering-inducing layer 31 are BPTT, the ordered growth of the copper phthalocyanine material may be induced by the van der Waals interaction (weak interaction) of the geometric channels on the surface of the BPTT film. Furthermore, due to the weak interaction between the BPTT film and the copper phthalocyanine film, there is only an orientation relationship between the two, and there is no strict lattice matching relationship, so that a copper phthalocyanine hole transport layer that is incommensurable with the first ordering-inducing layer 31 can be fabricated.

[0053] 1, in practical applications, according to the material properties of the hole transport layer 32 to be grown, the first ordering-inducing layer 31 may be made of a material that is compatible with and has strong interaction with the hole transport layer 32. For example, when the material of the hole transport layer 32 is nickel oxide, the inducing material contained in the first ordering-inducing layer 31 may be zinc oxide. When the material of the hole transport layer 32 is Cz2T, the inducing material molecule contained in the first ordering-inducing layer 31 may be BPTT.

[0054] For ease of understanding, the process in which the first ordering-inducing layer 31 induces the ordered growth of the hole transport layer 32 will be described by taking BPTT as an example. FIG. 2 shows the molecular structure diagrams of BPTT and Cz2T. As shown in FIG. 2, BPTT is a rigid rod-like molecule that is easy to form a highly ordered film on the surface of the tunnel composite layer 20, and the benzene rings of its end groups form geometric channels with specific orientations on the surface of the crystal array. When the hole transport layer 32 made of Cz2T material is grown on the surface of the first ordering-inducing layer 31 made of BPTT material, there exists van der Waals interaction between the hydrogen atoms on the benzene rings on the periphery of the Cz2T molecules and the benzene rings in the geometric channels formed by the BPTT material, which induces the Cz2T molecules to grow along the geometric channels of BPTT. In the process of Cz2T molecules growing along the geometrical channels of BPTT, the van der Waals interaction between Cz2T molecules and BPTT molecules is a weak interaction, and there is an orientation relationship between the growth of Cz2T molecules and the BPTT first ordering-inducing layer 31, so that the Cz2T molecules are stacked orderly along the geometrical channels formed by the BPTT molecules to form a highly ordered hole transport layer 32. In addition, there is no strict lattice matching relationship between Cz2T molecules and BPTT molecules, so that the thickness of the hole transport layer 32 is avoided from being affected by the first ordering-inducing layer 31.

[0055] From the above, it is found that the hole transport layer 32 can grow in an ordered manner and has a high crystallinity and a large crystal grain size due to the buffering and inducing effects of the first ordering-inducing layer 31. In this case, the hole transport layer 32 has few defects and good hole transport performance. Furthermore, the first ordering-inducing layer 31, as an intermediate layer between the hole transport layer 32 and the tunnel composite layer 20, can reduce the energy level difference between the films and achieve an energy level matching between the hole transport layer 32 and the tunnel composite layer 20 that is favorable for hole transport, thereby improving the hole transport performance of the tandem solar cell.

[0056] Based on the above, as shown in Figure 1, the second ordering-inducing layer 33 is formed on the hole transport layer 32. The process for forming the second ordering-inducing layer 33 can be one or more of magnetron sputtering process, laser pulse deposition process, thermal evaporation deposition process, chemical vapor deposition process, solution deposition process, gel-sol deposition process or hydrothermal nanoparticle synthesis process.

[0057] The second ordering-inducing layer 33 manufactured by the above method may have a thickness of 1 nm to 20 nm. For example, the second ordering-inducing layer 33 has a thickness of 1 nm, 5 nm, 8 nm, 10 nm, 12 nm, 18 nm, 20 nm, etc.

[0058] As shown in Fig. 1, the above-mentioned perovskite absorption layer 34 is formed on the second ordering-inducing layer 33. The method of forming the perovskite absorption layer 34 may include the steps of forming lead iodide and cesium bromide on the hole transport layer 32 by co-evaporation deposition, coating a mixture solution of formamidine iodide and formamidine hydrobromide on the lead iodide and cesium bromide to form a perovskite material film, and annealing the perovskite material film to form the perovskite absorption layer 34.

[0059] The thickness of the above-mentioned perovskite absorption layer 34 may be 250 nm to 1000 nm, but may be set according to the actual situation. The thickness of the perovskite absorption layer 34 may be 250 nm, 350 nm, 500 nm, 700 nm, 800 nm, 900 nm, 1000 nm, etc.

[0060] The material of the perovskite absorber layer 34 may include one or more perovskite materials, which have the general chemical formula ABX3, where A is one or more of the following cations: CH3NH3, C4H9NH3, NH2=CHNH2, and Cs cations, B is one or two of Pb2+ and Sn2+, and X is one or more of Cl-, Br-, and I-.

[0061] As shown in Fig. 1, the perovskite absorption layer 34 is formed on the second ordering-inducing layer 33 and has a specific orientation, phase state and ordered aggregation state structure. The second ordering-inducing layer 33 provides an interface buffer, induces the ordered growth of the upper perovskite absorption layer 34, manufactures a highly ordered perovskite absorption layer 34, improves the energy level matching between the hole transport layer 32 and the perovskite absorption layer 34, and enhances the hole transport performance.

[0062] In order to form a second ordering-inducing layer 33 with a high degree of order and to give the second ordering-inducing layer 33 a good ordering-inducing effect, an organic ammonium salt or an inorganic lead compound having properties similar to those of a perovskite material may be used as the inducing material.

[0063] When the inducing material of the second ordering-inducing layer is an organic ammonium salt or an inorganic lead compound, the organic ammonium salt and the inorganic lead compound have a high degree of match in crystal structure with the perovskite material of the perovskite absorption layer 34 and similar properties, and are therefore easy to induce the growth of a highly ordered perovskite absorption layer 34.

[0064] As shown in FIG. 1, in practical applications, the organic ammonium salt may be ammonium acetate, etc. The inorganic lead compound may be one or more of lead oxide, lead bromide, lead iodide, lead chloride, lead acetate, lead thiocyanate, and lead sulfide. These inorganic lead compounds are metal oxides and have good compatibility with the metal oxide hole transport layer 32, so that good interface contact can be achieved between the second ordering-inducing layer 33 and the hole transport layer 32. In addition, the inorganic lead compounds and the perovskite material of the perovskite absorption layer 34 are both lead compounds and have good compatibility with each other, so that the second ordering-inducing layer 33 is more likely to induce the growth of the perovskite absorption layer 34.

[0065] From the above, it has been found that the perovskite absorption layer 34 grows on the second ordering-inducing layer 33, and the buffering effect of the second ordering-inducing layer 33 allows the perovskite absorption layer 34 to avoid the adverse effects of the disorder of the surface molecules of the hole transport layer 32. In addition, the perovskite absorption layer 34 can grow in an ordered manner due to the induction effect of the second ordering-inducing layer 33, and has a high crystallinity and a large crystal grain size. In this case, the perovskite absorption layer 34 has few defects and a high photoelectric conversion efficiency. Furthermore, the second ordering-inducing layer 33, as an intermediate layer between the hole transport layer 32 and the perovskite absorption layer 34, can reduce the energy level difference between the films, achieve an energy level matching favorable for hole transport, and improve the hole transport performance of the tandem solar cell.

[0066] 1, in order to transport photogenerated carriers, an electron transport layer 35 may be further provided between the transparent conductive layer 36 and the perovskite absorption layer 34. The material of the electron transport layer 35 may be SnO2 or the like.

[0067] As shown in Fig. 1, the above-mentioned transparent conductive layer 36 is formed on the electron transport layer 35 to collect the photo-generated carriers. Of course, if the electron transport layer 35 is omitted, the transparent conductive layer 36 may be directly formed on the perovskite absorber layer 34. The material of the transparent conductive layer 36 may be one or more of transparent metal oxides, such as tin-doped indium oxide (ITO), zinc-doped indium oxide (IZO), tungsten-doped indium oxide (IWO), titanium-doped indium oxide (ITIO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), etc.

[0068] The above is a tandem solar cell according to an embodiment of the present disclosure, except that an electrode 37 should be formed on the front and back surfaces of the tandem solar cell, i.e., the transparent conductive layer 36 and the surface of the bottom cell 10 away from the perovskite top cell.

[0069] The embodiment of the present disclosure further provides a method for manufacturing the above-mentioned tandem solar cell. Specifically, the manufacturing method is described below by taking the p-type crystalline silicon-perovskite tandem solar cell shown in FIG. 3 as an example, and the steps of the manufacturing method are specifically as follows:

[0070] 4, a p-type crystalline silicon wafer 11 is provided. The p-type crystalline silicon wafer 11 is polished, texturized, and cleaned in this order to form a p-type crystalline silicon wafer 11 having a textured surface.

[0071] 5, a diffusion process such as ion implantation is used to form an n-type highly doped layer 12 on the surface of a p-type crystalline silicon wafer 11 having a textured surface. In this case, the p-type crystalline silicon wafer 11 has a pn junction, and the structure obtained in the above steps is defined as a bottom cell 10.

[0072] As shown in FIG. 6, a tunnel composite layer 20 made of a transparent metal oxide material is formed on the surface (bottom cell 10) having the p-n junction of a p-type crystalline silicon wafer 11 by a PECVD process, a magnetron sputtering process, a hot filament chemical vapor deposition process or a catalytic chemical vapor deposition process.

[0073] As shown in FIG. 7, a first ordering-inducing layer 31 having a thickness of 1 nm to 20 nm is formed on the tunnel composite layer 20 by a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process, or a nanoparticle synthesis process using a hydrothermal method.

[0074] As shown in Figure 8, a hole transport layer 32 having a thickness of 5 nm to 100 nm is formed on the first ordering-inducing layer 31 by a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process, or a nanoparticle synthesis process using a hydrothermal method.

[0075] As shown in Figure 9, a second ordering-inducing layer 33 having a thickness of 1 nm to 20 nm is formed on the hole transport layer 32 by a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process, or a nanoparticle synthesis process using a hydrothermal method.

[0076] 10, a perovskite absorption layer 34 having a thickness of 250 nm to 1000 nm is formed on the second ordering-inducing layer 33. Specifically, the following steps are included.

[0077] JPEG0007606599000001.jpg25170

[0078] A mixture solution of formamidine iodide (FAI) and formamidine hydrobromide (FABr) is applied onto the lead iodide and cesium bromide, and the mixture solution of FAI and FABr reacts with the lead iodide and cesium bromide to form a perovskite material film. The solvent of the mixture solution of FAI and FABr can be ethanol or isopropanol.

[0079] The perovskite material film is annealed at a temperature of 100°C to 200°C for 5 min to 30 min to form the perovskite absorption layer 34. The material component of the perovskite absorption layer 34 is CsxFA1-xPb(BryI1-y)3, and the thickness of the perovskite absorption layer 34 may be 100 nm to 1000 nm.

[0080] 11, an electron transport interface layer 351 having a thickness of 0.1 nm to 10 nm and a leakage current repair layer 352 having a thickness of 1 nm to 20 nm are formed on the perovskite absorption layer 34 by a thermal evaporation process. The material of the electron transport interface layer 351 may be LiF. The material of the leakage current repair layer 352 may be C60 or a fullerene derivative (PCBM).

[0081] 12, by using any one of a chemical vapor deposition process, a physical vapor deposition process, an atomic layer deposition process, and a solution deposition process, an electron transport layer 35 having a thickness of 1 nm to 30 nm is formed on the leakage current repair layer 352. The material of the electron transport layer 35 may be SnO2.

[0082] As shown in FIG. 13, a transparent conductive layer 36 made of a transparent metal oxide material and having a thickness of 30 nm to 200 nm is formed on the electron transport layer 35 by a magnetron sputtering process.

[0083] As shown in FIG. 14, an electrode 37 (having a thickness of 100 nm to 500 nm) made of silver is formed on the bottom cell 10 and the transparent conductive layer 36 by silk screen printing or a mask deposition process.

[0084] In order to verify the performance of the tandem solar cell according to the embodiment of the present disclosure, the embodiment will be described below by comparing it with a comparative example.

[0085] Example 1 The p-type crystalline silicon-perovskite tandem solar cell of this embodiment includes a p-type crystalline silicon bottom cell, a tunnel composite layer, a first ordering-inducing layer made of BPTT material, a hole transport layer made of Cz2T material, a second ordering-inducing layer made of lead bromide material, a perovskite absorption layer, an electron transport interface layer, a leakage current repair layer, an electron transport layer, and a transparent conductive layer, which are stacked in sequence. Specifically, the method for manufacturing the p-type crystalline silicon-perovskite tandem solar cell according to this embodiment is as follows. Step 1: providing a p-type crystalline silicon wafer, which is polished, texturized and cleaned in sequence to form a p-type crystalline silicon wafer having a textured surface; Step 2, an n-type highly doped layer is formed on the surface of a p-type crystalline silicon wafer having a textured surface by an ion implantation process. Step 3: A tunnel composite layer of ITO material is formed on the p-n junction side (bottom cell) of the p-type crystalline silicon wafer by magnetron sputtering process. Step 4, a first ordering-inducing layer (having a thickness of 1 nm) of BPTT material is formed on the tunnel composite layer by a thermal evaporation deposition process. Step 5: forming a hole transport layer (having a thickness of 5 nm) of Cz2T material on the first ordering-inducing layer by thermal evaporation deposition process. Step 6: A second ordering-inducing layer (having a thickness of 1 nm) made of lead bromide material is formed on the hole transport layer by magnetron sputtering process. Step 7: forming a perovskite absorption layer on the second ordering-inducing layer, which specifically includes: Lead iodide and cesium bromide are formed on the second ordering-inducing layer by co-evaporation deposition, where the formation rate of cesium bromide (CsBr) is 0.05A / s, the formation rate of lead iodide (PbI2) is 0.1A / s, and the total thickness is 250nm. A mixture solution of formamidine iodide (FAI) and formamidine hydrobromide (FABr) is applied onto the lead iodide and cesium bromide, and the mixture solution of FAI and FABr reacts with the lead iodide and cesium bromide to form a perovskite material film. The solvent of the mixture solution of FAI and FABr can be ethanol or isopropanol. The perovskite material film is annealed at a temperature of 100° C. for 30 min to form a perovskite absorber layer. The material composition of the perovskite absorber layer is CsxFA1-xPb(Bryl1-y)3, and the thickness of the perovskite absorber layer may be 250 nm. Step 8: Form an electron transport interface layer (having a thickness of 0.1 nm) made of LiF material and a leakage current repair layer (having a thickness of 1 nm) made of C60 material on the perovskite absorber layer by a thermal evaporation process. Step 9: Form an electron transport layer (having a thickness of 1 nm) made of SnO2 material on the leakage current repair layer by atomic layer deposition process. Step 10: A transparent conductive layer (30 nm) made of IWO material is formed on the electron transport layer by magnetron sputtering process. Step 11: Form an electrode (100 nm thick) made of silver on the bottom cell and the transparent conductive layer by silk screen printing.

[0086] Example 2 The p-type crystalline silicon-perovskite tandem solar cell of this embodiment includes a p-type crystalline silicon bottom cell, a tunnel composite layer, a first ordering-inducing layer made of zinc oxide material, a hole transport layer made of nickel oxide material, a second ordering-inducing layer made of lead oxide material, a perovskite absorption layer, an electron transport interface layer, a leakage current repair layer, an electron transport layer, and a transparent conductive layer, which are stacked in sequence. Specifically, the method for manufacturing the p-type crystalline silicon-perovskite tandem solar cell according to this embodiment is as follows. Step 1: providing a p-type crystalline silicon wafer, which is polished, texturized and cleaned in sequence to form a p-type crystalline silicon wafer having a textured surface; Step 2, an n-type highly doped layer is formed on the surface of a p-type crystalline silicon wafer having a textured surface by an ion implantation process. Step 3: A tunnel composite layer of FTO material is formed on the p-n junction side (bottom cell) of the p-type crystalline silicon wafer by magnetron sputtering process. Step 4, a first ordering-inducing layer (having a thickness of 20 nm) made of zinc oxide material is formed on the tunnel composite layer by magnetron sputtering process. Step 5: forming a hole transport layer (having a thickness of 100 nm) made of nickel oxide on the first ordering-inducing layer by magnetron sputtering process. Step 6: A second ordering-inducing layer (having a thickness of 20 nm) made of lead oxide material is formed on the hole transport layer by magnetron sputtering process. Step 7: forming a perovskite absorption layer on the second ordering-inducing layer, which specifically includes: Lead iodide and cesium bromide are formed on the second ordering-inducing layer by co-evaporation deposition, where the formation rate of cesium bromide (CsBr) is 0.2A / s, the formation rate of lead iodide (PbI2) is 10A / s, and the total thickness is 1000nm. A mixture solution of formamidine iodide (FAI) and formamidine hydrobromide (FABr) is applied onto the lead iodide and cesium bromide, and the mixture solution of FAI and FABr reacts with the lead iodide and cesium bromide to form a perovskite material film. The solvent of the mixture solution of FAI and FABr can be ethanol or isopropanol. The perovskite material film is annealed at a temperature of 200°C for 5 min to form a perovskite absorber layer. The material composition of the perovskite absorber layer is CsxFA1-xPb(BryI1-y)3, and the thickness of the perovskite absorber layer is 1000 nm. Step 8: Form an electron transport interface layer (having a thickness of 10 nm) made of LiF material and a leakage current repair layer (having a thickness of 20 nm) made of PCBM material on the perovskite absorber layer by a thermal evaporation process. Step 9: Form an electron transport layer (having a thickness of 30 nm) made of SnO2 on the leakage current repair layer by atomic layer deposition process. Step 10: A transparent conductive layer (200 nm) made of IzO material is formed on the electron transport layer by magnetron sputtering process. Step 11: Form an electrode (500 nm thick) made of silver on the bottom cell and the transparent conductive layer by silk screen printing.

[0087] Example 3 The p-type crystalline silicon-perovskite tandem solar cell of this embodiment includes a p-type crystalline silicon bottom cell, a tunnel composite layer, a first ordering-inducing layer made of zinc oxide material, a hole transport layer made of nickel oxide material, a second ordering-inducing layer made of lead iodide material, a perovskite absorption layer, an electron transport interface layer, a leakage current repair layer, an electron transport layer, and a transparent conductive layer, which are stacked in sequence. Specifically, the method for manufacturing the p-type crystalline silicon-perovskite tandem solar cell according to this embodiment is as follows. Step 1: providing a p-type crystalline silicon wafer, which is polished, texturized and cleaned in sequence to form a p-type crystalline silicon wafer having a textured surface; Step 2, an n-type highly doped layer is formed on the surface of a p-type crystalline silicon wafer having a textured surface by an ion implantation process. Step 3: A tunnel composite layer of ITO material is formed on the p-n junction side (bottom cell) of the p-type crystalline silicon wafer by PECVD process. Step 4, a first ordering-inducing layer (having a thickness of 8 nm) made of zinc oxide material is formed on the tunnel composite layer by a laser pulse deposition process. Step 5: forming a hole transport layer (having a thickness of 60 nm) made of nickel oxide on the first ordering-inducing layer by magnetron sputtering process. Step 6: A second ordering-inducing layer (having a thickness of 8 nm) made of lead iodide material is formed on the hole transport layer by a laser pulse deposition process. Step 7: forming a perovskite absorption layer on the second ordering-inducing layer, which specifically includes: Lead iodide and cesium bromide are formed on the second ordering-inducing layer by co-evaporation deposition, where the formation rate of cesium bromide (CsBr) is 0.1A / s, the formation rate of lead iodide (PbI2) is 3A / s, and the total thickness is 500nm. A mixture solution of formamidine iodide (FAI) and formamidine hydrobromide (FABr) is applied onto the lead iodide and cesium bromide, and the mixture solution of FAI and FABr reacts with the lead iodide and cesium bromide to form a perovskite material film. The solvent of the mixture solution of FAI and FABr can be ethanol or isopropanol. The perovskite material film is annealed at a temperature of 120°C for 20 min to form a perovskite absorber layer. The material composition of the perovskite absorber layer is CsxFA1-xPb(BryI1-y)3, and the thickness of the perovskite absorber layer is 500 nm. Step 8: Form an electron transport interface layer (having a thickness of 5 nm) made of LiF material and a leakage current repair layer (having a thickness of 10 nm) made of PCBM material on the perovskite absorber layer by a thermal evaporation process. Step 9: Form an electron transport layer (having a thickness of 12 nm) made of SnO2 material on the leakage current repair layer by chemical vapor deposition process. Step 10: A transparent conductive layer (50 nm) of IZO material is formed on the electron transport layer by magnetron sputtering process. Step 11: Form an electrode (250 nm thick) made of silver on the bottom cell and the transparent conductive layer by silk screen printing.

[0088] Example 4 The p-type crystalline silicon-perovskite tandem solar cell according to this embodiment includes a p-type crystalline silicon bottom cell, a tunnel composite layer, a first ordering-inducing layer made of BPTT material, a hole transport layer made of copper phthalocyanine material, a second ordering-inducing layer made of ammonium acetate material, a perovskite absorption layer, an electron transport interface layer, a leakage current repair layer, an electron transport layer, and a transparent conductive layer, which are stacked in sequence. Specifically, the method for manufacturing the p-type crystalline silicon-perovskite tandem solar cell according to this embodiment is as follows. Step 1: providing a p-type crystalline silicon wafer, which is polished, texturized and cleaned in sequence to form a p-type crystalline silicon wafer having a textured surface; Step 2, an n-type highly doped layer is formed on the surface of a p-type crystalline silicon wafer having a textured surface by an ion implantation process. Step 3: A tunnel composite layer of AZO material is formed on the p-n junction side (bottom cell) of the p-type crystalline silicon wafer by PECVD process. Step 4, a first ordering-inducing layer (having a thickness of 16 nm) made of BPTT material is formed on the tunnel composite layer by magnetron sputtering process. Step 5: forming a hole transport layer (having a thickness of 80 nm) made of copper phthalocyanine material on the first ordering-inducing layer by thermal evaporation deposition process. Step 6: A second ordering-inducing layer (having a thickness of 16 nm) made of ammonium acetate is formed on the hole transport layer by a laser pulse deposition process. Step 7: forming a perovskite absorption layer on the second ordering-inducing layer, which specifically includes: Lead iodide and cesium bromide are formed on the second ordering-inducing layer by co-evaporation deposition, where the formation rate of cesium bromide (CsBr) is 0.15A / s, the formation rate of lead iodide (PbI2) is 7A / s, and the total thickness is 800nm. A mixture solution of formamidine iodide (FAI) and formamidine hydrobromide (FABr) is applied onto the lead iodide and cesium bromide, and the mixture solution of FAI and FABr reacts with the lead iodide and cesium bromide to form a perovskite material film. The solvent of the mixture solution of FAI and FABr can be ethanol or isopropanol. The perovskite material film is annealed at a temperature of 180°C for 20 min to form a perovskite absorber layer. The material composition of the perovskite absorber layer is CsxFA1-xPb(BryI1-y)3, and the thickness of the perovskite absorber layer is 800 nm. Step 8: Form an electron transport interface layer (having a thickness of 9 nm) made of LiF material and a leakage current repair layer (having a thickness of 18 nm) made of C60 material on the perovskite absorber layer by a thermal evaporation process. Step 9: Form an electron transport layer (having a thickness of 17 nm) made of SnO2 material on the leakage current repair layer by physical vapor deposition process. Step 10: A transparent conductive layer (100 nm) made of ITO material is formed on the electron transport layer by magnetron sputtering process. Step 11: Form an electrode (300 nm thick) made of silver on the bottom cell and the transparent conductive layer by silk screen printing.

[0089] Comparative Example 1 The p-type crystalline silicon-perovskite tandem solar cell of this comparative example has the same structure as the tandem solar cell described in Example 1, except that the first ordering-inducing layer made of BPTT material and the second ordering-inducing layer made of lead bromide material are omitted. The manufacturing method of the p-type crystalline silicon-perovskite tandem solar cell according to this comparative example is the same as that of Example 1, and therefore will not be described in detail here.

[0090] Comparative Example 2 The p-type crystalline silicon-perovskite tandem solar cell of this comparative example has the same structure as the tandem solar cell described in Example 1, except that the first ordering-inducing layer made of BPTT material is omitted. The manufacturing method of the p-type crystalline silicon-perovskite tandem solar cell according to this comparative example is the same as that of Example 1, and therefore will not be described in detail here.

[0091] Comparative Example 3 The p-type crystalline silicon-perovskite tandem solar cell of this comparative example has the same structure as the tandem solar cell described in Example 1, except that the second ordering-inducing layer made of lead bromide material is omitted. The manufacturing method of the p-type crystalline silicon-perovskite tandem solar cell according to this comparative example is the same as that of Example 1, and therefore will not be described in detail here.

[0092] In order to verify the performance of the tandem solar cell, the performance parameters such as photoelectric conversion efficiency, fill factor (FF), open circuit voltage (VOC), and short circuit current (JSC) of the devices manufactured in Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and the comparison of the performance parameters is shown in Table 1.

[0093] Table 1 Comparison of performance parameters of each tandem solar cell JPEG0007606599000002.jpg60170

[0094] As can be seen from the above examples, comparative examples and Table 1, when the first ordering-inducing layer or the second ordering-inducing layer is installed separately, the photoelectric conversion efficiency is improved, but in the tandem solar cell in which both the first ordering-inducing layer and the second ordering-inducing layer are installed, the photoelectric conversion efficiency is significantly improved, mainly due to the increase in fill factor (FF) and open circuit voltage (Voc). Therefore, by using the first ordering-inducing layer and the second ordering-inducing layer, the crystal performance of the hole transport layer and the perovskite absorption layer is improved, which is favorable for the separation and transport of photogenerated carriers, and the accumulation and combination of electrons and holes in the tandem solar cell is reduced.

[0095] In describing the above embodiments, the particular features, structures, materials, or characteristics may be combined in any suitable manner in any one or more of the embodiments or examples.

[0096] The above are only specific embodiments of the present disclosure, and the scope of protection of the present disclosure is not limited thereto, and any changes or replacements that a person skilled in the art can easily think of within the technical scope disclosed in the present disclosure shall be included in the scope of protection of the present disclosure. Therefore, the scope of protection of the present disclosure should be in accordance with the scope of protection of the claims.

Claims

1. a bottom cell having a textured surface; a hole transport layer formed on the textured surface of the bottom cell; a second ordering inducer and a perovskite absorber layer formed on the hole transport layer, the second ordering inducer being located between the hole transport layer and the perovskite absorber layer; A transparent conductive layer formed on the perovskite absorber layer, the inducing material contained in the second ordering-inducing layer is ammonium acetate or an inorganic lead compound; the inorganic lead compound is one or more of lead oxide, lead bromide and lead iodide; The general chemical formula of the material of the perovskite absorption layer is ABX 3 and A is CH 3 N.H. 3 Cation, C 4 H 9 N.H. 3 Cation, NH 2 = CHNH 2 cation, Cs cation, and B is Pb 2+ , Sn 2+ and X is one or two of the following: - , B - , I - One or more of the following: a first ordering-inducing layer positioned between the bottom cell and the hole transport layer; The first ordering-inducing layer contains a rod-shaped molecular material, and the hole transport layer is made of an organic hole transport material; or The first ordering-inducing layer contains a metal oxide as an inducing material, and the hole transport layer contains an inorganic hole transport material; the rod-shaped molecular material is BPTT, the metal oxide is zinc oxide; the first ordering-inducing layer has a thickness of 1 nm to 20 nm; A tandem solar cell comprising:

2. 2. The tandem solar cell of claim 1, wherein the second ordering-inducing layer has a thickness of 1 nm to 20 nm.

3. 3. The tandem solar cell according to claim 1, wherein the material of the hole transport layer comprises one or more of PTAA, Cz2T, Spiro-OMeTAD, Spiro-TTB, copper phthalocyanine, and nickel oxide.

4. 3. The tandem solar cell according to claim 1, wherein the hole transport layer has a thickness of 5 nm to 100 nm.

5. The method for manufacturing a tandem solar cell according to claim 1 or 2, characterized in that the process for forming the second ordering-inducing layer and the hole transport layer is one or more of a magnetron sputtering process, a laser pulse deposition process, a thermal evaporation deposition process, a chemical vapor deposition process, a solution deposition process, a gel-sol deposition process, or a nanoparticle synthesis process by a hydrothermal method.

6. The method of forming the perovskite absorber layer comprises: forming lead iodide and cesium bromide on the second ordering-inducing layer by co-evaporation deposition; coating a mixture solution of formamidine iodide and formamidine hydrobromide on the lead iodide and cesium bromide to form a perovskite material film; and annealing the perovskite material film to form a perovskite absorber layer.

Citation Information

Patent Citations

  • Perovskite planar heterojunction solar battery based on self-assembled monolayer

    CN104465992A

  • Organic and inorganic hybrid perovskite-based solar cell and method for manufacturing same

    CN104795499A

  • Perovskite solar cell and preparation method thereof

    CN105609641A

  • Perovskite thin-film solar cell and preparation method thereof

    CN107104189A

  • Solar cell and preparation method thereof and method for improving transmission characteristic of perovskite layer

    CN109411607A